Estimating the Impact of the Financial Development on Energy Consumption: A Co-integration Analysis - Dumrul, Yasemin (International Journal of Energy Economics and Policy, 2018)
This paper investigated the impact of financial development on energy consumption in Turkey. For this purpose, the annual data from 1961 to 2015 is examined using with Johansen Cointegration Test and Fully Modified Ordinary Least Square (FMOLS) and Dynamic Ordinary Least Square (DOLS) Test. Test results indicate the existence of long run relationship between financial development, economic growth and energy consumption in Turkey. In addition The FMOLS and DOLS test results show that financial development and economic growth have a positive effect on energy consumption in Turkey. For this reason, policy makers should also take into account the impact of financial development on energy consumption while setting energy policies and setting targets. Keywords: Financial Development, Energy Consumption, Economic Growth, Co-integration, Turkey. JEL Classifications: C32, Q43 DOI: https://doi.org/10.32479/ijeep.6836